Thyroid (dys-)function in normal and disturbed pregnancy - Ziegelmüller, Brigitte Katharina; Ditsch, Nina; Jeschke, Udo; Gärtner, Roland; Toth, Bettina (Archives of gynecology and obstetrics, 2013)
During pregnancy, physiologic changes in maternal thyroid function take place especially due to hormonal as well as metabolic processes. Human chorionic gonadotropin activates the maternal thyroid gland leading to increased thyroid hormone production. A sufficient availability of maternal thyroid hormones is essential for fetal development, especially during the first trimester of pregnancy, when the fetal thyroid gland is not yet functional.
Published online: 27 October 2012
Gesehen am 27.11.2020